Orange blossom & honey : magical Moroccan recipes from the souks to the Sahara - Gregory-Smith, John (Kyle Books, 2018)
In researching this book, John traveled into the heart of the High Atlas Mountains to learn the secrets of traditional lamb barbecue, then journeyed north, through the city of Fez, where the rich dishes of the Imperial Courts are still prepared in many homes. From here he continued on to the Rif Mountains, where rustic recipes are made with the freshest seasonal produce. From Moroccan-style paella, cooked in the blue town of Chefchaouen, to stuffed Berber breads baked in the hot desert sands, John has discovered the real food of the country, learning from the locals to reveal little-known dishes, which he then gives his modern twist. The chapters include Streetfood, Salads & Vegetables, Meat & Poultry, Seafood, Tagines and Desserts, plus a section of spice mixes and marinades from chermoula to harissa. With mouthwatering recipes, breathtaking location photography and John's infectious enthusiasm, this is an essential addition to every cook's collection.